Prioritization of Watersheds for Perspective Landuse Planning Using Remote Sensing and Geographic Information System - Dutta, Dibyendu; Das, S N; Sharma, J R; Kudrat, M; Manchanda, M L (Annals of Arid Zone, 2016)
Present study envisages the usefulness of soil information, derived from enhanced geocoded digital remote sensing data of IRS LISS II (Scale I: 50,000), in combination with terrain slope, and watershed information generated from topographical maps (I :50,(00), and aerial photographs (1: 25,000) tor assessment of severity of soil erosion in 125 micro-watershed of Kishanganj tehsil of Rajasthan. Thematic maps on soil, watershed and slope werc digitized using AutoCAD software and converted to image file for working at ARC/INFO GIS environment. Area weighted averages of different soil types within the watersheds were ranked according to their erodibility and integrated with slope information and delivery ratio to arrive at Sedimcnt Yield Index (SYI) values, which were further grouped into lour categories (very high, high, medilUll and low). Terrain physiography and soil data obtained from intcipretation ,U1d analysis of remotely sensed data can be effectively used in the framework of Imld evaluation for qualitatively asscssing soil erosion hazard and priority watersheds.